Multiphysics modelling of lack-of-fusion voids formation and evolution in IN718 made by multi-track/multi-layer L-PBF - Bayat, Mohamad; Mohanty, Sankhya; Hattel, Jesper Henri (International journal of heat and mass transfer, 2019)
•A multiphysics numerical model of the multi-layer L-PBF process is developed for the first time.•The CFD model consists of a multi-phase flow that includes evaporation, melting and solidification.•A DEM model based on the Lagrangian framework is implemented to simulate the powder-feeding.•Lack-of-fusion zones become smaller in the subsequent layers, due to heat accumulation from the sintered layers.•Porosity decreases in the next layers, due to better heat fluid flow conditions caused by elevated temperatures.•Elongated pores are formed parallel to the laser track and are vertically aligned in the cross-sections. Laser-based powder bed fusion (L-PBF) is a branch of additive manufacturing technology which is considered to be a superior process due to its capability of producing complex designs with low material waste. Despite L-PBFs various unique characteristics, manufactured parts still suffer from a wide variety of defects, among which porosity is one of the most important. In this paper, a multiphysics numerical model for the multi-track/multi-layer L-PBF is developed and used for analysing the formation and evolution of voids caused by lack of fusion and improper melting. The multiphysics model is in meso-scale and is used to track and observe the formation of porosities, and considers phenomena such as multi-phase flow, melting/solidification, radiation heat transfer, capillary and thermo-capillary (Marangoni effect) forces, recoil pressure, geometry dependant absorptivity and finally evaporation and evaporative cooling. A novel methodology has been introduced to model the two subsequent powder-laying and fusion processes, for each layer, by means of a discrete element method (DEM) in a Lagrangian framework and a computational fluid dynamics (CFD) model, both implemented in Flow-3D. The results for the investigated process parameters indicate that the porosities (voids) are mainly formed in between the tracks, largely due to improper fusion of the particles. Moreover, it is observed that the pores are mostly elongated in the direction parallel to the laser scanning paths, as expected. The probability of the presence of pores is also observed to be higher in the first layer, where the average layer temperature is lower as well. Furthermore, the lack of fusion zones are seen to become smaller in the subsequent layers, largely due to better fluid flow and higher temperatures, because of heat accumulation in those layers.